2013
DOI: 10.1158/1078-0432.ccr-12-2251
|View full text |Cite
|
Sign up to set email alerts
|

Pralatrexate Pharmacology and Clinical Development

Abstract: Folates are well known to be essential for many cellular processes, including cellular proliferation. As a consequence, antifolates, the fraudulent mimics of folic acid, have been shown to be potent therapeutic agents in many cancers. Over the past several decades, efforts to improve on this class of drugs have met with little success. Recently, one analog specifically designed to have high affinity for the reduced folate carrier, which efficiently internalizes natural folates and antifolates, has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…Numerous other antifolates have since been synthesized and tested preclinically, in many cases drawing from the enhanced understanding of the pharmacology and biology of MTX or AMT, including their membrane transport, polyglutamylation, and binding to intracellular targets. In recent years, a new generation of clinically relevant antifolates has emerged including PDX Thompson, 2009;Marchi et al, 2013), RTX (Wilson and Malfair Taylor, 2009), and PMX (Hazarika et al, 2005;Cohen et al, 2009) (Fig. 1).…”
Section: Role Of Antifolates In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other antifolates have since been synthesized and tested preclinically, in many cases drawing from the enhanced understanding of the pharmacology and biology of MTX or AMT, including their membrane transport, polyglutamylation, and binding to intracellular targets. In recent years, a new generation of clinically relevant antifolates has emerged including PDX Thompson, 2009;Marchi et al, 2013), RTX (Wilson and Malfair Taylor, 2009), and PMX (Hazarika et al, 2005;Cohen et al, 2009) (Fig. 1).…”
Section: Role Of Antifolates In Cancer Therapymentioning
confidence: 99%
“…The net result was increased drug efficacy toward leukemia, breast cancer, and nonsmall-cell lung cancer cell lines in vitro and in vivo. In phase I and phase II trials, including patients with non-small-cell lung cancer (Krug et al, 2003) and peripheral T-cell lymphoma (O'Connor et al, 2009;Marchi et al, 2013), PDX showed efficacy and safety. The Food and Drug Administration (FDA) approved the use of PDX in 2009 for the treatment of relapsed, refractory peripheral T-cell lymphoma (Thompson, 2009).…”
Section: Role Of Antifolates In Cancer Therapymentioning
confidence: 99%
“…Many of these agents have demonstrated limited to no activity in B-cell malignancies while demonstrating marked activity in T-cell lymphoma. One such example is pralatrexate (Folotyn Ò ), which was the first drug approved for patients with relapsed or refractory PTCL in 2009 [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…6 Pralatrexate (PDX) is a 10-deaza-aminopterin antifolate that was rationally designed to improve cellular uptake and intracellular retention compared with MTX. [7][8][9][10][11][12][13] It enters cancer cells via the reduced folate carrier (RFC-1), which is overexpressed in cancer cells compared with normal cells. PDX is a high-affinity substrate for RFC-1, and it is more efficiently taken into cells at a rate 14 times greater than MTX.…”
mentioning
confidence: 99%
“…The recommended phase 2 doses of single-agent PDX given every other week in trials of patients with nonhematologic malignancies have ranged from 150 mg/m 2 to 190 mg/m 2 with vitamin supplementation. 13,[18][19][20] The initial generation of trials evaluating either MTX or trimetrexate with 5-FU used bolus 5-FU, which is less effective compared with infusional schedules. An every-other-week schedule of leucovorin-modulated 5-FU has been widely tested, and is reported to be well tolerated.…”
mentioning
confidence: 99%